Re-evaluating the Realist Conception of War as a Business Metaphor - MacFarlane, Bruce (Teaching business ethics, 1999)
The state of war is a popular metaphor employed by many business writers seeking to explain the imperatives of strategic decision-making. It is a metaphor which draws on a “realist” characterisation of war as a Hobbesian state of nature devoid of a moral dimension. However, the work of Walzer (1977) has demonstrated that rules of war, established over generations and across cultural divides, play a significant role in the conduct of warfare. Through identifying and analysing rules of war in parallel with ethical dilemmas in business life, such as whistleblowing, it is possible to develop a more sophisticated understanding of the war metaphor in place of simplified, state of nature realism. This alternative version of the war metaphor is a useful means of introducing students to Aristotlean virtues as well as challenging their preconceptions about the nature of business activity.